Risk-based weight of evidence assessment of commercial sharks in western Australia. (1st May 2021) - Braccini, Matias; Hesp, Alex; Molony, Brett
Abstract: Sharks are generally taken in multispecies fisheries worldwide so in many cases it is logistically infeasible and cost prohibitive to assess the impact on all species caught. Risks of fishing impacts to the sustainability of shark species were assessed using a weight of evidence risk-based framework. Whiskery ( Furgaleus macki ), gummy ( Mustelus antarcticus ), dusky ( Carcharhinus obscurus ), and sandbar ( C. plumbeus ) sharks provide a good case study as they are the main ( 80% of the catch) shark species taken in Western Australia (WA) and represent the range of life history strategies of other shark species typically caught. Based on the available lines of evidence for stock status (spatial and temporal time series of catch, effort, catch rates, size composition and population modelling), the 2015–16 risk level for the four species was scored as medium―i.e. it is unlikely (5–20% chance) that there is a high level of stock depletion. The status of each of the four species was scored as 'acceptable' with risk control measures in place, indicating that no additional restrictions are required. Graphical abstract: The main commercial shark species of Western Australia have a moderate sustainability riskTheir status is acceptable so no further management restrictions are required. Image 1 Highlights: A large proportion of shark populations is considered to be in high risk mostly due to overfishing. The information required for traditional fisheries stock assessments is not available for the vast majority of species. We assessed the main commercial shark species in Western Australia using a risk-based weight-of-evidence approach (WoEA). The current risk level for the four species is medium, i.e. it is unlikely that there is a high level of stock depletion. Our study exemplifies the use of WoEA for the assessment of shark stocks.